1985
DOI: 10.1073/pnas.82.11.3596
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of substitutions on the p21 proteins.

Abstract: The conformational effects of different amino acid substitutions (lysine, serine, proline, and D-valine) for glycine at position 12 in the p21 oncogene-encoded proteins have been investigated by using conformational energy calculations. The normal cellular gene codes for a glycine at position 12 in the amino acid sequence, in the middle of a hydrophobic p21-(6-15)-decapepetide from Leu-6 to Gly-15. Mutations that cause amino acid substitutions for Gly-12 result in a protein product that produces malignant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…They are believed to play an essential role in growth and/or development. A number of structural comparisons and structure predictions have been published in an attempt to explain the structural implications of the amino acid replacements at positions 12, 13 and 59,61, which lead to tumorigenic activation of the protein (Gay and Walker, 1983;Wierenga and Hol, 1983; Leberman and Egner, 1984;Halliday, 1983;Pincus and Brandt-Rauf, 1985;Murakami, 1985). Since secondary structure predictions at the very best are only 60% accurate and are sometimes contradictory to each other, the actual determination of the three-dimensional structure is essential.…”
Section: Introductionmentioning
confidence: 99%
“…They are believed to play an essential role in growth and/or development. A number of structural comparisons and structure predictions have been published in an attempt to explain the structural implications of the amino acid replacements at positions 12, 13 and 59,61, which lead to tumorigenic activation of the protein (Gay and Walker, 1983;Wierenga and Hol, 1983; Leberman and Egner, 1984;Halliday, 1983;Pincus and Brandt-Rauf, 1985;Murakami, 1985). Since secondary structure predictions at the very best are only 60% accurate and are sometimes contradictory to each other, the actual determination of the three-dimensional structure is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies (13)(14)(15)(16) in which the preferred conformations of the amino-terminal peptide were explored using conformational energy calculations (16), it was found that substitution of any L-amino acid, except Pro, for Gly-12 (which occupies this position in the normal protein) caused a well-defined change in the structure of the peptide, irrespective of the substituting amino acid. This change was such that a chain-reversal (bend) conformation, that occurred at Ala-11-Gly-12 in the normal protein, now occurred at Xaa-12-Gly-13, where Xaa is the amino acid substituting for Gly-12.…”
mentioning
confidence: 99%
“…This change was such that a chain-reversal (bend) conformation, that occurred at Ala-11-Gly-12 in the normal protein, now occurred at Xaa-12-Gly-13, where Xaa is the amino acid substituting for Gly-12. The peptides with arbitrary amino acid substitutions at position 12 could not adopt the normal lowest energy Ala-11-Gly-12 bend, whereas the "normal" peptide could adopt the lowestenergy structure for the substituted peptides, i.e., a bend at positions 12 and 13, at a sacrifice of several kcal (1 cal = 4.184 J) in conformational energy (14,15). On the basis of these results, it was predicted that P21 proteins containing any L-amino acid, except Pro, at position 12, would cause malignant transformation of cells (14,15) and that high intracellular concentrations of the normal protein would likewise cause cell transformation since significant levels of the alternate "malignancy-causing" conformation (bend at positions 12 and 13) would then be expressed (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations